Infections in the era of immunobiologicals - Romiti, Ricardo (2024)
Immunobiologicals represent an innovative therapeutic option in dermatology. They are indicated in severe and refractory cases of different diseases when there is contraindication, intolerance, or failure of conventional systemic therapy and in cases with significant impairment of patient quality of life. The main immunobiologicals used in dermatology basically include inhibitors of tumor necrosis factor-alpha (anti-TNF), inhibitors of interleukin-12 and -23 (anti-IL12/23), inhibitors of interleukin-17 and its receptor (anti-IL17), inhibitors of interleukin-23 (anti-IL23), rituximab (anti-CD20 antibody), dupilumab (anti-IL4/IL13) and intravenous immunoglobulin. Their immunomodulatory action may be associated with an increase in the risk of infections in the short and long term, and each case must be assessed individually, according to the risk inherent to the drug, the patient general condition, and the need for precautions. This article will discuss the main risks of infection associated with the use of immunobiologicals, addressing the risk in immunocompetent and immunosuppressed patients, vaccination, fungal infections, tuberculosis, leprosy, and viral hepatitis, and how to manage the patient in the most diverse scenarios.